Selective Harmonic Elimination in Reduced-Switch Multilevel Inverters for PV Systems Using the Sparrow Search Algorithm - Baraa, Saif Mohamed; Desa, Hazry; Mohammed, Karar Saeed; Al-Malaisi, Taha Abdulsalam; Hussain, Abadal-Salam Taha; Majdi, Hasan S. (Universitas Muhammadiyah Yogyakarta, 2025)
International Medium voltage and high-power systems use MLIs with low harmonic distortion voltage wave forms in medium voltage systems. Nevertheless, implementation of conventional MLI topologies appears to face various issues such as enhanced system complexity, costs, and conduction losses for specific switching frequencies as well as increased switching frequency leading to impractical solutions in RE systems. Based on the above analysis, this work introduces a three-phase, seven-level RS MLI topology applicable to photovoltaic (PV) systems. The proposed RS MLI has fewer switch devices than a typical topology to achieve cost optimizations without compromising the features of precise topologies. In an attempt to improve on the design of the RS MLI, the Selective Harmonic Elimination (SHE) method is implemented to minimize THD and switching losses. Iterative solutions can be delicate depending on the configuration of the SHE’s and more so for higher level configurations. Thus, for solving the problem the Sparrow Search Algorithm (SSA), is developed to serve as the new optimization method. SSA is thus compared with Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) using MATLAB/SIMULINK simulations with modulation indices of 0.1, 0.5 and 1.0. It is established from the result that proposed strategic swarm approach (SSA) yields better accuracy, fast convergence speed and improves the THD of the system compared to GA and PSO. However, there is still the question of computational complexity, which seems to entail studying the RS MLI in different conditions as an open problem for future work. The innovation made by this work can help to enhance RS MLI designs to better feasible for use in renewable energy systems.